2006
DOI: 10.1096/fj.05-5258fje
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 increases LIM kinase activity by promoting its homo‐dimerization

Abstract: LIM kinase 1 (LIMK1) is a serine protein kinase that regulates the actin cytoskeleton by phosphorylation and inactivation of actin depolymerizing factor cofilin. LIMK1 activity is regulated by the Rho-GTPases via their serine/threonine kinase effectors Rho-kinase and p21-activated kinases 1 and 4 that phosphorylate LIMK1 on threonine 508 in its activation loop. The purpose of this study was to elucidate the pathway leading to the stability of LIMK1, a protein with a half-life of approximately 20 h. Because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 27 publications
3
39
0
2
Order By: Relevance
“…Protein Swo1, a fission yeast analog of hsp90, facilitates myosin II assembly (41). Conversely, inhibition of hsp90 attenuates or abolishes its effects on the actomyosin cytoskeleton (38)(39)(40)(41). In the present study, TGF-b1-induced hyperpermeability was associated with increased hsp27 phophorylation and hsp90-hsp27 complex formation; both of these effects were prevented by radicicol.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Protein Swo1, a fission yeast analog of hsp90, facilitates myosin II assembly (41). Conversely, inhibition of hsp90 attenuates or abolishes its effects on the actomyosin cytoskeleton (38)(39)(40)(41). In the present study, TGF-b1-induced hyperpermeability was associated with increased hsp27 phophorylation and hsp90-hsp27 complex formation; both of these effects were prevented by radicicol.…”
Section: Discussionsupporting
confidence: 45%
“…Interaction of hsp90 with N-WASP protects N-WASP from proteasome-dependent degradation, and by promoting v-Src-dependent N-WASP phosphorylation, amplifies N-WASP-dependent actin polymerization (39). Hsp90 also stabilizes/activates LIM kinase, promoting actin polymerization by inactivation of the actin depolymerizing factor, cofilin (40). Protein Swo1, a fission yeast analog of hsp90, facilitates myosin II assembly (41).…”
Section: Discussionmentioning
confidence: 99%
“…1A, endogenous HSP90 coprecipitated, albeit weakly, with wtMET. Previous reports by us and others have suggested that the activated states of some HSP90-dependent kinases have a greater dependence on HSP90 (31)(32)(33). To determine if this were the case for MET, we compared the degree of wtMET-HSP90 interaction in the presence and absence of the MET ligand HGF.…”
Section: Wild-type Met Is An Hsp90-dependent Kinasementioning
confidence: 99%
“…The dimerization of receptors induces autophosphorylation in the kinase domain of the Trk receptors, followed by the activation of various signaling pathways (35). Coincidentally, the activity and stability of LIMK1 is also regulated by homo-dimerization (36). LIMK1 homo-dimerization could induce its transphosphorylation and thus increase LIMK1 activity.…”
Section: Trkb/limk1 Interaction Contributes To Axonal Elongationmentioning
confidence: 99%